Fetal–Maternal Hemorrhage Detected by Sudden Disappearance of Rh Immune Globulin–Related Anti-D. Issue 6 (December 2015) - King, Jennifer R.; Zeger, Gary D.; Plaza, Natalie; Lee, Richard H.; Shulman, Ira A.
Abstract : BACKGROUND: Fetal–maternal hemorrhage is usually spontaneous and goes undetected but can be associated with adverse perinatal outcomes. CASE: We describe the detection of a fetal–maternal hemorrhage by abrupt disappearance of prophylactic anti-D on antibody screen in an Rh-negative mother with dichorionic twins admitted for atrial flutter of one twin. Both rosette and Kleihauer-Betke tests were positive. The diagnosis was confirmed by anemia in one twin at birth. CONCLUSION: Fetal–maternal hemorrhage requires a high index of suspicion for diagnosis. An unexpected sudden decline in Rh immune globulin–related anti-D may be an indication of fetal–maternal hemorrhage. Abstract : The diagnosis of fetal–maternal hemorrhage should be considered with a sudden rapid decline in Rh immune globulin–related anti-D.